BoNT clinical trial update: Sialorrhea. (April 2023) - Tamadonfar, Emily T.; Lew, Mark F.
Abstract: Sialorrhea is the excessive accumulation of saliva, a prevalent symptom among a number of neurologic conditions in both pediatric and adult patients. Over the years, the management of sialorrhea has evolved and included a variety of interventions, ranging from nonpharmacologic, pharmacologic, and surgical treatment options. The most common option for treatment has been the use of botulinum toxin injections in the management of sialorrhea. While there have been several clinical trials to assess the efficacy of botulinum toxin in the treatment of sialorrhea, the largest randomized control trials to date have been with incobotulinumtoxin (2019) and rimabotulinumtoxin (2020) which show consistent reduction in salivary flow rate and improvement in clinical outcomes with comparable duration of treatment effectiveness. In this update, we review the evolution of treatment and injection methods for sialorrhea among many neurologic diseases. We discuss the challenges in evaluating and measuring efficacy in clinical trials for sialorrhea and compare the contemporary botulinum toxin clinical trials in the treatment of sialorrhea. Highlights: Two serotypes of botulinum toxin have been FDA-approved for sialorrhea. The largest trials have been with incobotulinumtoxinA and rimabotulinumtoxinB. A challenge to study design is finding valid objective measures for sialorrhea.